Analysis of Financial Literacy Levels and Their Relationship with the Characteristics of Coconut Farmers in Pangi Village, Parigi Moutong Regency - Ziad Fad Wafi; Farid; Henni Mande (Universitas Muhammadiyah Palu, 2026)
This study aims to analyse the level of financial literacy and its relationship with the characteristics of coconut farmers in Pangi Village, Parigi Moutong Regency. This type of research is quantitative with a descriptive and correlational approach. According to data from the Central Bureau of Statistics, the study population comprised 192 coconut farmers from Pangi Village, distributed across three hamlets. The sample size was determined using the Slovin formula and stratified random sampling. Data analysis was conducted using descriptive and correlational analyses. Based on the descriptive analysis, the financial literacy level had an average score of 82.57%. The results of the correlation analysis showed that the relationship between age and financial literacy level was r = -0.375; p = 0.002, the relationship between education and financial literacy level was r = 0.565; p = 0.000, the relationship between income and financial literacy level was r = 0.311; p = 0.011, and the relationship between farming experience and financial literacy level was r = 0.002; p = 0.985. The results showed that the financial literacy level of coconut farmers in Pangi Village, Parigi Moutong Regency, is classified as high, and there is a significant relationship between age, education level, and income with the financial literacy level of coconut farmers in Pangi Village, Parigi Moutong Regency. Meanwhile, the farming experience variable did not show a significant relationship.